การเปิดรับข่าวสารเกี่ยวกับปัญหาการทารุณกรรมสัตว์ ความรู้ ความตระหนักและการสนับสนุนองค์กรเอกชนที่ช่วยเหลือและสงเคราะห์สัตว์ - พัชรา ระบบกิจการดี (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purposes of this research is to study media exposure to animal-abusing problems, the correlation among media exposure, knowledge, awareness and support for nongovernmental organizations for animalrelated help. Questionnaires were used to collect data from a total of 462 samples. Frequency, percentage, mean, t- test, One-way ANOVA and Pearson’s Product Moment Correlation Coefficient were used for data analysis. SPSS for windows program was used for data processing. The results of the study are as follows: 1. Most people are exposed to information on problem of animal-abusing via mass media specialized and interpersonal media at low level. Their support for non-governmental organizations for animal related help are also at low level. However their knowledge are moderate and awareness are high. 2. People different in sex and income are exposed to specialized and interpersonal media differently. Those different in age and occupation are exposed to specialized media differently. People with different in education are exposed to interpersonal media differently. 3. Media exposure to animal-abusing problems by mass, specialized and interpersonal media are negatively correlated with knowledge of animal-abusing problems and the performance of non-governmental organizations for animal- related help. 4. Media exposure to animal-abusing problems via mass, specialized and interpersonal media are not correlatedsignificantly with their awareness regarding animal-abusing problems and the non-governmental organizations for animal-related help. 5. Media exposure to animal-abusing problems on mass,specialized and interpersonal media are positively correlated with their support to non-governmental organizations for animal-related help. 6. Knowledge are positively correlated with their awareness regarding animal-abusing problems and the importance of non-governmental organizations for animal related help. 7. Knowledge are negatively correlated with their support to non-governmental organizations for animal-related help. 8. Awareness are not correlated significantly with their support to non-governmental organizations for animal-related help. 9. Media exposure to animal-abusing problems and the performance of the non-governmental organizations for animal-related help via interpersonal media is the best explain their support for non-governmental organizations for animal-related help.